2002
DOI: 10.1124/jpet.301.3.838
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Blood-Brain Tumor Barrier Permeability by Calcium-Activated Potassium Channels

Abstract: The blood-brain tumor barrier (BTB) limits the delivery of therapeutic drugs to brain tumors. We demonstrate in a rat brain tumor (RG2) model an enhanced drug delivery to brain tumor following intracarotid infusion of bradykinin (BK), nitric oxide (NO) donors, or agonists of soluble guanylate cyclase (sGC) and calcium-dependent potassium (K Ca ) channels. We modulated K Ca channels by specific agonists and agents that produce NO and cGMP in situ to obtain sustained enhancement of selective drug delivery to bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
144
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 32 publications
13
144
0
Order By: Relevance
“…By using quantitative autoradiographic method to quantify the radioactivity in the tumor area, the BTB permeability for [ 14 C]-AIB could be accurately measured. By using this animal model, NS1619 was found to increase BTB permeability and iberiotoxin could decrease BTB permeability (Ningaraj et al, 2002). It was also found that infusion NS1619 with bradykinin could selectively enhance BTB permeability in brain tumors, not in normal brain (Hu et al, 2007).…”
Section: Targeting Ionic Channels In Animal Modelsmentioning
confidence: 80%
“…By using quantitative autoradiographic method to quantify the radioactivity in the tumor area, the BTB permeability for [ 14 C]-AIB could be accurately measured. By using this animal model, NS1619 was found to increase BTB permeability and iberiotoxin could decrease BTB permeability (Ningaraj et al, 2002). It was also found that infusion NS1619 with bradykinin could selectively enhance BTB permeability in brain tumors, not in normal brain (Hu et al, 2007).…”
Section: Targeting Ionic Channels In Animal Modelsmentioning
confidence: 80%
“…[ 14 C]sucrose was used as the tracer to measure tumor permeability as described previously (7,8,11). In brief, saline was infused into the femoral vein at a rate of 66.7 AL/min for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…To study the duration of permeability increase by L-arginine or hydroxyurea, K i was measured at different time points from 30 to 120 min after the oral treatments (200 mg/kg L-arginine and 80 mg/kg hydroxyurea). Previous studies suggest an important role of K Ca channels in regulation of BTB permeability (11). Additional rats were infused with iberiotoxin (0.26 Ag/kg/min), a K Ca channel antagonist, to investigate whether inhibition of K Ca channels by iberiotoxin attenuates permeability increases induced by NO donors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated that this increased transport was not mediated through tight junction opening but rather through enhanced vesicular transport . The authors further reported that the overexpressed calcium-dependent potassium (K Ca ) channels and the ATP-sensitive potassium (K ATP ) channel in tumor capillaries were responsible for the enhanced transport activity (Ningaraj et al, 2003;Ningaraj et al, 2002). These data suggest another approach is needed for specific drug delivery to brain tumors.…”
Section: Other Molecular Eventsmentioning
confidence: 99%